REMAKE, HISTORIA E IDEOLOGÍA: HOLLYWOOD Y ADIÓS A LAS ARMAS DE ERNEST HEMINGWAY - Dr. Alberto José LENA ORDÓÑEZ (Fonseca, Journal of Communication, 2023)
This article analyses David O. Selznick’s 1957 adaptation of Ernest Hemingway’s A Farewell to Arms. In trying to shed light on the historical and ideological context of Selznick’s production, it shall be placed emphasis upon the influence of Frank Borzage’s previous adaptation of Hemingway’s work. This essay will also stress Selznick’s ambitions, that is, the fact that he wanted to emulate and improve the former adaptation of the novel. In spite of this, the comparison between both films reveals that the melodramatic structure of Selznick’s remake stems from the structure of Borzage’s film. Moreover, Selznick’s production could be seen as a case in point of the role played by deshistorization in cinematic remake.